NUMERICAL MODELING OF DETERMINING THE ROCKWELL HARDNESS NUMBER OF A STEEL SAMPLE - Riumin, V.; Solodovnyk, Yu. (Municipal economy of cities. Series: «Economy science», 2024)
In steel Hardness is a mechanical property that indicates the resistance of a material to local plastic deformation caused by mechanical indentation. In engineering, hardness is mainly used to determine the properties of various materials. In mechanical solids, the study of the hardness of materials is usually limited to the study of metals and their mechanical behavior. To understand the mechanism of hardness in metal structures, a basic understanding of materials science is necessary. Accurate hardness measurement is of great practical importance in the technical diagnosis of potentially hazardous industrial equipment (pipelines, pressure vessels, metal structures). This is primarily due to the fact that this characteristic has a strong correlation with strength and yield strength, which largely determine the possibility of further operation of the equipment. At the same time, one of the main advantages of hardness measurement is the speed of its determination and the non-destructive nature of its control. A finite element model was developed for the indentation process, and the contact radius and contact pressure were obtained. The Rockwell hardness measurement process was modelled in accordance with the test methodology of DSTU ISO 6508-1:2013. The indentation process was modelled using ANSYS software with different contact models and different loads. The relevance of solving the problem of modelling the process of determining the surface hardness number using the FEM software ANSYS is determined by the high degree of automation of the solution process. During the modelling, it is assumed that the material of the sample into which the indenter of any shape is pressed is homogeneous isotropic and elastoplastic according to the kinematic plasticity model. This model corresponds to the behavior of steels. In addition, the indenter material is isotropic and linearly elastic. In the developed numerical model, the indenter is taken in the form of a tungsten carbide ball, which corresponds to the scheme for determining the hardness number on the "B" scale. In conditions of limited access to laboratory equipment, numerical modelling of the process of determining the hardness number allows students to demonstrate all stages of the test at a qualitatively new level, and further, to compare with the results of full-scale tests.